Nonlinear waves and instabilities leading to secondary reconnection in reconnection outflows. (14th February 2018) - Lapenta, Giovanni; Pucci, Francesco; Olshevsky, Vyacheslav; Servidio, Sergio; Sorriso-Valvo, Luca; Newman, David L.; Goldman, Martin V.
Abstract : Reconnection outflows have been under intense recent scrutiny, from in situ observations and from simulations. These regions are host to a variety of instabilities and intense energy exchanges, often even superior to the main reconnection site. We report here a number of results drawn from an investigation of simulations. First, the outflows are observed to become unstable to drift instabilities. Second, these instabilities lead to the formation of secondary reconnection sites. Third, the secondary processes are responsible for large energy exchanges and particle energization. Finally, the particle distribution function are modified to become non-Maxwellian and include multiple interpenetrating populations.